Farm Business Management: Analysis of Farming Systems - Nuthall, Peter L (CABI, 2014)
Every farmer likes to think s/he operates an optimal farming system, a system that more than likely will be different from any other farmer’s optimal systems. Each farm is unique in its set of resources (quantity and quality) and the objectives held by the farmer and family. For each farmer, and his advisors, the challenge is to work out this optimal system, though, given the nature of farming and primary production, there could well be a number of systems that are near optimal which for all intents and purposes can be called optimal alternatives. This book is about the methods available to determine optimal systems. Some might be used by farmers themselves, but more likely by farm advisors and consultants, and by farm management researchers interested in, firstly, providing farmers with guidance on optimal systems, and, secondly, providing govern- ments with advice on the impact of farm policy measures. The methods are all about problem solving, as any decision situation implies choice and, therefore, requires a method for deciding which alternative maximizes the objectives. The book is not, however, about carrying out the optimal plans (for a coverage of the skills required in practical farm management, see Nuthall, 2010).